Afrikaners and the Boundaries of Faith in Post-Apartheid South Africa - Teppo, Annika Björnsdotter (Routledge Contemporary South Africa Ser., 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface and acknowledgements -- Introduction: Mixed blessings -- 1. The Afrikaners and their church -- 2. Performing whiteness -- 3. Cracked laer -- 4. The changing religious scene in Stellenbosch -- 5. Madams and masters of magic -- 6. "We kept everything, and we changed everything" -- Conclusion: South African miracles -- Index.